Critical roles for LIGHT and its receptors in generating T cell-mediated immunity during Leishmania donovani infection. - Amanda C Stanley; Fabian de Labastida Rivera; Ashraful Haque; Meru Sheel; Yonghong Zhou; Fiona H Amante; Patrick T Bunn; Louise M Randall; Louise M Randall; Klaus Pfeffer; Stefanie Scheu; Michael J Hickey; et al. (PLoS Pathogens)
LIGHT (TNFSF14) is a member of the TNF superfamily involved in inflammation and defence against infection. LIGHT signals via two cell-bound receptors; herpes virus entry mediator (HVEM) and lymphotoxin-beta receptor (LTβR). We found that LIGHT is critical for control of hepatic parasite growth in mice with visceral leishmaniasis (VL) caused by infection with the protozoan parasite Leishmania donovani. LIGHT-HVEM signalling is essential for early dendritic cell IL-12/IL-23p40 production, and the generation of IFNγ- and TNF-producing T cells that control hepatic infection. However, we also discovered that LIGHT-LTβR interactions suppress anti-parasitic immunity in the liver in the first 7 days of infection by mechanisms that restrict both CD4(+) T cell function and TNF-dependent microbicidal mechanisms. Thus, we have identified distinct roles for LIGHT in infection, and show that manipulation of interactions between LIGHT and its receptors may be used for therapeutic advantage.